Enzyme and microwave co-assisted extraction, structural characterization and antioxidant activity of polysaccharides from Purple-heart Radish. (15th March 2022) - Lin, Yuyang; Pi, Jiaju; Jin, Peiyi; Liu, Yingtao; Mai, Xiaoman; Li, Pingfan; Fan, Huajun
Highlights: Simultaneous biphasic extraction of different polysaccharides from Purple-heart Radish with an ATPS. Integration of EAE, MAE and ATPE in a one-step procedure for improvement of extraction efficiency. Optimization of EAE-MAATPE process with single-factor experiments and response surface methodology. FT-IR, HPLC characterization of structures and compositions of two polysaccharides. The polysaccharides extracted exhibited stronger antioxidant and anti-lipid peroxidation activities in vitro. Abstract: A novel method of simultaneous extraction and separation of diverse polysaccharides from Purple-heart Radish was developed by integrating EAE with MAATPE. The effects of different enzymes, the ATPS composition, extraction temperature, time etc. were investigated by single-factor experiments and RSM. Under the optimum conditions, the extraction yields of PTP, PBP and total polysaccharides were 9.107 ± 0.391%, 32.506 ± 0.046% and 41.613 ± 0.437%, respectively. By means of HPGPC and PMP-HPLC, Mw of PTP and Mw of PBP were 15935 Da and 27962 Da, respectively. PTP and PBP were mainly composed of mannose, glucuronic acid, aminogalactose, glucose, galactose and arabinose. Moreover, both polysaccharides exhibited stronger antioxidant activities for scavenging multiple radicals and anti-lipid peroxidation. Compared to the conventional extraction methods, EAE-MAATPE achieved higher extraction efficiency due to the synergistic effect between EAE and MAATPE leading to rupture and enzymolysis of cell. Thus, EAE-MAATPE provided an efficient alternative to simultaneous extraction of different polysaccharides from natural products.